Time Series Models - Harvey, Andrew C. (MIT Press, 2012)
The revisions in this edition are substantial. There have been important developments in time series in the last ten years, and this has led to the addition of sections on topics such as non-linear models, fractional differencing, unit roots and co-integration. Furthermore, in the light of experience gained teaching from the book there has been some rearrangement and change in emphasis. Thus the multivariate material is gathered together in a single chapter, and the miscellaneous regression topics of what was the last chapter have been dropped or worked into other sections. The chapter on modelling, formerly chapter 6, has been completely re-worked. This is partly because ARIMA methodology is now less dominant than it was when the first edition was written. In economic applications in particular, the use of unrestricted autoregressions, with associated tests for unit roots, has become popular, partly because of the way it leads into classes of multivariate models which are able to take account of long-run relationships between trending variables. In addition, structural time series models, which are models formulated directly in terms of components of interest, such as trends, seasonals and cycles, have advanced considerably.